Determinan Simpanan Dana Pihak Ketiga Bank Syariah: Adakah Dampak Turbulansi Ekonomi? - Hasanah, Uswatun; Lutfi, Lutfi (Universitas Islam Negeri Alauddin Makassar, 2024)
The economic turbulence caused by the Covid-19 outbreak does not seem to have a negative impact on bank third party deposits. This research aims to examine the impact of economic turbulence, sharia financing, bank size, capital, and profitability on third party funds. This research uses quarterly data from ten Islamic banks in Indonesia from 2017 - 2022. The data is analyzed using panel data analysis techniques, with the best model of random effects. The results prove that economic turbulence negatively impacts the deposits of the sharia banks. Bank capital decreases sharia bank deposits, while sharia financing increases the deposits. The research did not find any significant influence of bank size and profitability on the third party funds. The effect of economic turbulence on deposits also applies when gross domestic product (GDP) growth is used as a substitute for the crisis dummy variable. GDP growth has a significant positive impact on third party deposits. These findings imply that the Government and Bank Indonesia need to maintain the stability of national economic growth. Sharia bank management needs to maintain the availability of third party funds in line with financing needs. This research also supports the business cycle theory regarding the negative impact of economic turbulence on bank business activities.